Behaviorally anchored rating scales in the performance management system within the centralized policing system in Indonesia - Rachmat, Faesal; Prasojo, Eko; Muslim, Muh Azis (Edelweiss Applied Science and Technology, 2025)
This study investigates the implementation of Behaviorally Anchored Rating Scales (BARS) in the centralized performance management system of the Indonesian National Police (Polri). The research aims to explore how BARS is operationalized and what challenges emerge within the institutional and cultural framework of Polri. A qualitative case study design was employed, utilizing in-depth interviews and document analysis to collect relevant data. Thematic analysis was applied to identify key patterns, challenges, and areas for improvement in BARS application. The findings indicate several barriers to effective implementation, including insufficient training for evaluators, the use of overly generic behavioral indicators, and the dominance of hierarchical relationships that compromise objectivity. These issues contribute to inconsistencies, limited transparency, and reduced strategic value in performance evaluations. The study concludes that without significant reform, the use of BARS will remain largely formalistic and fail to support meaningful performance improvement. Practical implications include the need for enhanced evaluator capacity building, better contextualization of behavioral indicators, and greater integration of performance data into strategic human resource planning. These adjustments are essential for strengthening organizational accountability, professional standards, and public trust in Indonesia’s law enforcement institutions.